Holocene Ice‐Flow Speedup in the Vicinity of the South Pole. Issue 13 (6th July 2018) - Lilien, David A.; Fudge, T. J.; Koutnik, Michelle R.; Conway, Howard; Osterberg, Erich C.; Ferris, David G.; Waddington, Edwin D.; Stevens, C. Max
Abstract: The South Pole Ice Core (SPICEcore) was drilled at least 180 km from an ice‐flow divide. Thus, the annual‐equivalent layer thicknesses in the core are affected by spatial variations in accumulation upstream in addition to temporal variations in regional accumulation. We use a new method to compare the SPICEcore accumulation record, derived by correcting measured layer thicknesses for thinning, with an accumulation record derived from new GPS and radar measurements upstream. When ice speeds are modeled as increasing by 15% since 10 ka, the upstream accumulation explains 77% of the variance in the SPICEcore‐derived accumulation (versus 22% without speedup). This result demonstrates that the ice‐flow direction and spatial pattern of accumulation were stable throughout the Holocene. The 15% speedup in turn suggests a slight (3–4%) steepening or thickening of the ice‐sheet interior and provides a new constraint on the evolution of the East Antarctic Ice Sheet following the glacial termination. Plain Language Summary: Understanding past changes in the flow of Antarctic ice is key to contextualizing modern glacier speedup and retreat, but there are few estimates of past flow speeds in the Antarctic interior. We used a new method to compare a direct record of the past 10, 000 years of snowfall accumulation near the South Pole, derived from layers in the new South Pole Ice Core, with an estimate of the snowfall upstream over the last 150 years. By seeing how these records correlate, we provide a new constraint on past ice flow in the region, showing that the flow direction has been unchanged for 10, 000 years while flow speeds have increased slightly during that time. This analysis also shows that most of the variations of layer thickness in the South Pole Ice Core result from ice flow rather than variations in accumulation through time. These results provide new data that can help improve models of ice flow over the last 10, 000 years. Key Points: We used a new method to combine ice core and geophysical measurements to constrain ice‐flow history near the South Pole over the past 10 ka Ice‐flow speeds in the 70‐km upstream of the South Pole increased by 15% during the Holocene Accumulation patterns and ice‐flow direction in the 70‐km upstream of the South Pole have remained nearly constant during the Holocene